Pengaruh Latihan Kelincahan Terhadap Kemampuan Dribbling pada Siswa Ekstrakurikuler Bola Basket di SMP Negeri 1 Lahat Selatan - Hardianti Novitasari; Daryono Daryono; Agung Mahendra (Pusat Riset dan Inovasi Nasional, 2024)
This study aims to determine the effect of agility training on dribbling abilities in basketball extracurricular students at SMP Negeri 1 Lahat Selatan. Agility training was chosen because it is an important aspect of basketball that can increase the speed and accuracy of movements, which greatly influences dribbling skills. This research uses an experimental method with a pre-test and post-test design. The research sample consisted of 20 students who took part in extracurricular basketball. The instrument used to measure dribbling ability is a standard dribbling test. The results of data analysis show that there is a significant increase in dribbling ability after being given agility training, as indicated by a significant difference in pre-test and post-test scores. Based on these results, it can be concluded that agility training has a positive influence on improving the dribbling abilities of basketball extracurricular students at SMP Negeri 1 Lahat Selatan.